To fill in the table, we can choose different values for x and then solve for y using the equation y + 4 = 3x.
Let's choose x = 0:
y + 4 = 3(0)
y + 4 = 0
y = -4
So when x = 0, y = -4.
Now let's choose x = 1:
y + 4 = 3(1)
y + 4 = 3
y = -1
So when x = 1, y = -1.
Lastly, let's choose x = 2:
y + 4 = 3(2)
y + 4 = 6
y = 2
So when x = 2, y = 2.
Now we can fill in the missing values in the table:
x | y
0 | -4
1 | -1
2 | 2
Use the equation y+4=3x
to fill in the missing values in the table below.
1 answer